The Spotted Nightjar Calls When Dingo Pups are Born: Ecological and Social Indicators in Central Australia. Issue Volume 33:Issues 1(2013) (March 2013) - Turpin, Myfany; Ross, Alison; Dobson, Veronica; Turner, M. K.
Across cultures there are known signs that signal the availability of certain foods, predict the weather or warn people of impending events. In Central Australia the call of the spotted nightjar ( Eurostopodus argus ) signals the time when dingo pups are born. This article identifies indicator events known by speakers of the Arandic languages in Central Australia. Indicator events can be described as the presence or behavior of a particular species or phenomenon that signals some other species or phenomenon. Arandic people group these into five broad domains: indicators of food, water, weather, danger and news (e.g., an imminent visitor). A diverse range of ecological, meteorological and human (bodily) phenomena serve as indicators, with birds being the most prevalent. This study explores the basis of indicator events, finding both an ecological and cultural basis for many signs. It also draws attention to the significance of the indicator relationship in terms of how people make sense of co-occurring events around them. We also consider some implications for natural resource management and phenology.